Assessment of Financial Condition in Companies Applying Circular Economy Principles - Šapalaitė, Toma; Kiaušienė, Ilona (Vilnius University Proceedings, 2023)
Extraction and use of raw materials have a significant impact on the environment by increasing energy consumption and CO2 emissions. Because of it, every year humans generate 2.5 billion tons of waste. In recent years, EU has been working on laws on waste management. In March 2020, the European Commission presented the circular economy plan, which involves more eco-friendly production and waste recycling. Special attention is paid towards sectors that require a lot of raw materials usage, e.g electronics, plastic, textile and construction. Being a great solution, the application of the circular economy principle still raises an essential question whether and how much it is effective. In order to achieve the set goals it’s necessary to constantly monitor the processes, therefore the evaluation of the efficiency of the circular economy and its impact on the company’s financial indicators is still a problem. The aim of this research is to develop a model for assessing the financial condition of companies applying circular economy principles. These are the main objectives that have been set: 1) describe the concept, theory and principles of circular economy after analysing the scientific literature; 2) summarise empirical studies after analysing the circular economy principles and the assessment of the financial conditions of companies. It was found that in order to evaluate how the implementation of the circular economy principles changes the financial condition of companies, different authors use different methods. It is emphasised that the financial condition of companies applying circular economy principles can be assessed using a composite indicator.
Keywords: circular economy; principles; financial conditions; company